Modelling and techno-economic analysis of a solar PV system for power supply: case study of a rural area in North-Eastern NIgeria. - Abdulkarim, Hauwa Talatu (Cranfield University, 2019)
Energy which is vital in the economic and social growth of any country is facing increased demand because of technological and industrial developments in the world. Most of the energy supplied globally is being generated from fossil fuels. However, studies have shown that these resources have many negative environmental and health impacts. This gives reason for development of renewable energy sources especially solar photovoltaic system. The investment for large solar PV power plants is capital intensive, therefore, a solar photovoltaic system model (SPVSM) which can be rapidly used for accurate sizing of the system components for optimized solar PV system for power supply becomes imperative. Soiling, which has not received adequate global attention, is a major problem in the operation of solar PV systems. It affects the performance of PV systems; therefore, the study of its impact is crucial especially for location with potential for dust accumulation. The main aim of this research is to develop a novel, simple and robust decision- making model, Solar-Photovoltaic-System-Model (SPVSM) for an optimised power supply at a competitive cost and to determine the impacts of dust accumulation on the performance of solar PV modules. The collection and analysis of solar and climatic data is of utmost importance to the development of solar energy conversion system in any location because the knowledge of the availability of solar resource is key to the decision on installation of solar PV systems. For this research, three locations (Maiduguri, Minna and Port Harcourt) were carefully chosen to represent the three radiation regions in Nigeria. This becomes very important because of the scanty availability of solar and climatic data analysis for these regions. Solar irradiance, relative humidity, temperature and sunshine hours data were collected for these locations for a period (2006 to 2016) from the Nigerian Meteorological Agency, Abuja. The data were statistically analysed using Minitab 17 software and Microsoft Excel. The SPVSM which was developed on a single graphical user interface platform in MATLAB17 is made up of six panels, each handling the sizing of different system components (PV modules, inverters, charge controllers and batteries) as well as energy and economic analysis of the system. A PV model which generates the I-V and P-V characteristics of the 50W module was developed using Simulink in MATLAB2017. A single diode model was used to produce the ideal equivalent circuit of solar cell, which is a current source in parallel with a single diode. Two sub-systems were developed to handle saturation current and photocurrent. A maximum power point tracking (MPPT) system was developed using thePerturb and Observe algorithm in Simulink. The specification of a 50 W PV module model TDG-PV T050M365 was used for the simulation. The MPPT simulation gave a 50.09 W for solar irradiance of 1000 W/m² and 37.9 W/m² for irradiance of 800 W/m². A field experiment was carried out in a location in North-eastern Nigeria to assess the impact of dust accumulation on the performance of PV modules. The experiment was conducted for 14 days using a 50W module of model TDG-PV T050M365. The current and voltage output of the module were concurrently measured and logged using Mooshimeter. The temperature, solar irradiance, wind speed and relative humidity were measured and recorded every hour. Dust were collected at different heights (50 cm, 100 cm, 150 cm and 200 cm).The dust so collected were analysed in Cranfield. For dust accumulation to have effect on performance of PV module, there must be adhesion. This led to the laboratory experimentation on the effect of temperature, particle size, humidity, type of sand, and height on the adhesion of sand to glass cover of PV module. The data analysis shows that the three locations have adequate daily solar irradiance and therefore, have potential for viable development of solar PV systems for power supply with Maiduguri being more viable than Minna and Port Harcourt. The economic analysis from the SPVSM shows that the Levelized cost of electricity is $0.081/kWh and the net present value (NPV) is positive for Maiduguri, therefore it can be concluded that development of solar PV system in Maiduguri is economically viable. The use of lower peak watt module rating has economic implications on the project total cost and consequently on the overall economics of the system. Dust accumulation can reduce the performance of solar PV module by more than 50% and the analysis of sand/dust samples from Maiduguri shows varying sizes and shapes of roundness that roll off the panel with less effect on the panel surface erosion; and sharpness that deteriorates the PV module. Also, the chemical analysis further shows that dust from Maiduguri is high in silica (SiO2) i.e. prevalence of quartz which confirm the zone being desert. The results of the laboratory experiments show that, some of the factors studied have effect on the amount of sand that sticks to glass. Humidity is the factor with the highest influence. At higher humidity more sand adhere to the glass, this is due to the higher moisture content of the air which aids in dissolving any soluble materials and bind the particles to the surface. Also, desert natural sands adhere more strongly to the glass than artificial quartz-based sands, this is possibly due to the fact that natural sand contains higher amounts of soluble materials.
Keywords: Dust; energy; humidity; irradiance; performance; temperature